Behavior of 321 stainless steel under engineering stress and strain controlled fatigue. (November 2016) - Prasad Reddy, G.V.; Dinesh, P.M.; Sandhya, R.; Laha, K.; Jayakumar, T.
Graphical abstract: Highlights: 321 SS has shown ratcheting-strain accumulation even under zero mean-stress. Direction of ratcheting is strongly dependent on initial-ramp direction of 1st-cycle. Plastic-strain range and striation-width are lower in strain-controlled fatigue. S-N curve of present study is 2–3 orders of magnitude lower than ASME best-fit curve. Abstract: Cyclic deformation and fracture behavior of the 321 stainless steel are investigated at 633 K under engineering-stress and strain controlled low cycle fatigue (LCF) cycling, and the fatigue life data are compared with ASME section-III Division-1 S-N curve. In stress-controlled LCF tests, ratcheting-strain accumulation is observed even under zero mean-stress, and the direction of ratcheting is found to strongly depend on initial-ramp direction of first-cycle. In addition, plastic-strain range and striation width are observed to be higher than those in strain-controlled tests. The stress-life curve obtained from stress-controlled tests is 2–3 orders of magnitude lower in comparison to stress-life curve derived from strain-controlled LCF tests as per the ASME procedure. The discrepancy is attributed to the differences in deformation and damage development in stress and strain-controlled cycling.